PENINGKATAN KETERAMPILAN MENULIS PROPOSAL DAN LAPORAN KEGIATAN PADA PEMUDA KARANG TARUNA DI KECAMATAN KOTA UTARA, KECAMATAN KOTA UTARA, KOTA GORONTALO - Ulfa Zakaria (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Youth empowerment can be a form of nation building. Youth groups through their focused spirit of building will become supporters of the creation of an advanced and creative society and works. Writing is one of the language skills that can express the author's thoughts. The ability to express ideas and thoughts in written form is supported by various factors, including linguistic competence and knowledge of the writing to be compiled. Formal script writing skills for within an organization become very urgent because it affects the acceptance of the intent and purpose of the writing to the audience of readers. To anticipate problems in the preparation of a script, this training was initiated for its implementation which was mixed into a community service program